Foreign Direct Investment and Specific Feature of their Accounting - Samuolis, Gediminas (Ekonomika, 2001)
The article presents the classification of foreign investment and their situation in Lithuania. One of the Lithuanian strategic priorities is the attraction foreign investment into the Lithuania and thus lakes part in the economic development making use of financial resources, modern technologies and management experience, creating new working places.The most importance of foreign investment is foreign direct investment. Author presents the structure of foreign direct investment and their accounting in enterprises. Especial attention author pays to the problem of consolidated financial statements and accounting for investments in subsidiaries. The production of consolidated financial statements (group accounts) is done on the basis that a group of enterprises is a single accounting entity.